Production of cellulase by Aspergillus niger under submerged and solid state fermentation using coir waste as a substrate - Mrudula,Soma (2011)
Aspergillus niger was used for cellulase production in submerged (SmF) and solid state fermentation (SSF). The maximum production of cellulase was obtained after 72 h of incubation in SSF and 96 h in Smf. The CMCase and FPase activities recorded in SSF were 8.89 and 3.56 U per g of dry mycelial bran (DBM), respectively. Where as in Smf the CMase & FPase activities were found to be 3.29 and 2.3 U per ml culture broth, respectively. The productivity of extracellular cellulase in SSF was 14.6 fold higher than in SmF. The physical and nutritional parameters of fermentation like pH, temperature, substrate, carbon and nitrogen sources were optimized. The optimal conditions for maximum biosynthesis of cellulase by A. niger were shown to be at pH 6, temperature 30 ºC. The additives like lactose, peptone and coir waste as substrate increased the productivity both in SmF and SSF. The moisture ratio of 1:2 (w/v) was observed for optimum production of cellulase in SSF.